Classification System and Case Definitions for SARS-CoV-2 Infection in Pregnant Women, Fetuses, and Neonates. Issue 1 (24th March 2021) - Shah, P.S.; Diambomba, Y.; Acharya, G.; Morris, S.K.; Bitnun, A.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:565–568) The vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from mother-to-fetus has been highly debated, and there are varied recommendations for testing and classifying parturients suspected of COVID-19 infection. Newborns with a coronavirus disease 2019 (COVID-19) infection may also pose danger to health care workers, particularly because some may not exhibit symptoms at birth. This paper examined the classification of pregnant women and neonates suspected or confirmed to have COVID-19 at the onset of labor and delivery.